Representation of Gender Roles in Koirala’s Narendra Dai - Bista, Asmita (JODEM: Journal of Language and Literature, 2020)
Bishweshwar Prasad Koirala‟s novel Narendra Dai is replete with gender issues of the then society that has marked its relevance even at the present time. This article examines how this novel has explored the concept of gender as a per formative entity; and shows that the characters perform the traditional gender roles because of the strict socio-cultural obligations. It also examines while performing the traditional gender roles, how the lives of these characters get affected. For that Judith Butler’s idea of gender theory has been used. Butler proposes theory of gender as a constant performance: a series of cues observed, internalized, and repeated over time. The significance of this study is to contribute a different perspective for the reader to see Narendra Dai because in this novel, Koirala has shown that since the characters cannot go against the social norms, they perform traditional gender roles via social policing and polishing. The study concludes that these characters define the socially prescribed gender roles because gender is socio-political construction that achieves legitimacy and naturality via perpetual observation and repetition.